O curso de Ciências Contábeis no Brasil - Paschoal, Alexandre Magno F.; Silva, Ana Maria Fontes da; Pereira, João Manoel de Oliveira; Fujol, Kátia de França; Lacerda, Márcia dos Reis; Santos, Paulo Maurício Tinoco dos (Contabilidade Vista & Revista, 2009)
O artigo não tem resumo.